Evaluation of Service Quality Through ITIL V3 Framework in the Service Design Domain (Case Study: Lazada Application) - Atika, Nur; Akso, Rafian Tri; Wulandari, Arini; Mubarok, Fawaz Asyar; Abdurrahman, Indra Kurniawan; Wahyudi, Dwi; Tarwoto, Tarwoto (International Journal of Informatics and Information Systems, 2024)
In the era of globalization and business digitalization, improving the quality of customer service is a crucial aspect for company success. Companies that are able to provide optimal and responsive service tend to maintain customer satisfaction and compete effectively in an increasingly tight market. Therefore, the use of the Information Technology Infrastructure Library (ITIL) framework is a strong foundation for managing and improving service quality. This research focuses on analyzing service quality in the ITIL V3 Service Design domain, by applying this framework to a significant e-commerce application, namely Lazada. Lazada, as a leading platform in Southeast Asia, has been an example of providing superior customer experience through its services. This research explains the role of ITIL in managing service quality, with an emphasis on the Service Design domain. This study uses a combination of methods, including literature study, questionnaire survey of Lazada users, and observation of application infrastructure. The analysis results show that Lazada has reached a high level of maturity in ITIL V3 Domain Service Design, with all subdomains reaching maturity level 4. However, there is room for improvement, especially in information security. The conclusion shows that Lazada can continue to maintain customer satisfaction and competitiveness in a competitive market by continuing to improve service quality, especially in aspects found through gap analysis.